Influence of Vineyard Vegetational Borders on Western Grape Leafhopper (Erythroneura elegantula Osborn), its Egg Parasitoids (Anagrus spp.) and Generalist Insect Predators - Costello, Michael J.; Thrupp, Ann; McGourty, Glenn (South African Journal of Enology and Viticulture, 2021)
Studies have shown that vegetational diversity in or around cropping systems can enhance natural enemy abundance, although the impact on herbivores is less certain. We studied the influence of vineyard vegetational borders on density of the western grape leafhopper, Erythroneura elegantula, its major parasitoids, Anagrus spp., and two generalist predators, Orius spp. and Leptothrips mali. Two study vineyards had planted, perennial flowering hedgerows, one bordered a natural riparian zone, and one had a sparse border of native trees. From April to September 2007, we counted leafhopper nymphs and adults of Anagrus spp., Orius spp. and L. mali within 10 m of the border, and at additional 20 m intervals up to 90 m. At two sites with a diverse border, leafhopper density was stable nearest the border; at other distances leafhopper density decreased between the first and second generations. This effect was not seen at the sparse border site. Anagrus spp. density was enhanced at one site with a diverse border, but only late season. There was no border effect on the generalist insect predators, by site or early vs. late season. Regression analysis showed a positive relationship between leafhopper and Anagrus spp. density, suggesting that the parasitoids were responding to higher leafhopper density. We conclude that, depending on the nature of the border vegetation, there can be an effect on leafhopper nymphal density, but in this study there is no evidence that it was due to natural enemies.